Thimber House at Lake Starnberg : Münsing, Germany 2000 - Fink + Jocher (2001)
Ampliación de una vivienda de fines del siglo XIX con vista al lago
Keywords: STARNBERG; ALEMANIA; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; CONSTRUCCION; MATERIALES; MADERA; AMPLIACION; VIVIENDAS EN LA COSTA; FINK, DIETRICH; JOCHER, THOMAS; GRAFL, IVAN